2009
DOI: 10.1007/bf03324915
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Brain Normative Archive of structural MR scans: norms for medial temporal atrophy and white matter lesions

Abstract: Persons in the IBNA study had clinical and neuropsychological features consistent with that of the general population. Their brain morphometric features may be used as normative references for patients with suspected neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In both AD (P < 0.001) and aMCI patients (P < 0.001), hippocampal volumes were decreased compared with that of a reference healthy elderly population [Galluzzi et al, 2009]. The individual mean hippocampal volumes were 1.5 SDs below the mean hippocampal volume of the reference group in 19/25 AD and 8/18 …”
Section: Associations With Hippocampal Volumementioning
confidence: 95%
See 1 more Smart Citation
“…In both AD (P < 0.001) and aMCI patients (P < 0.001), hippocampal volumes were decreased compared with that of a reference healthy elderly population [Galluzzi et al, 2009]. The individual mean hippocampal volumes were 1.5 SDs below the mean hippocampal volume of the reference group in 19/25 AD and 8/18 …”
Section: Associations With Hippocampal Volumementioning
confidence: 95%
“…An experienced radiologist reviewed the severity of the cerebrovascular disease according to the Wahlund rating scale [Wahlund et al, 2001]. Subjects were excluded when the Wahlund rating scale was above the 90th percentile of the distribution from a previously published healthy elderly population [Galluzzi et al, 2009]. The local ethics committee approved the study.…”
Section: Subjectsmentioning
confidence: 99%
“…As for the specific reasons for MRI referral for the patients in this sample, past clinical history analyses showed that those reasons were not unevenly related to specific sociodemographic variables, global cognition, depressive symptoms or other clinical features (Galluzzi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The imaging acquisition was carried out at the Neuroradiology Unit of the "Città di Brescia" Hospital, Brescia (Italy), from March 2001 to December 2008, and includes data from outpatients examined for reasons unrelated to cognition (Riello et al, 2005;Galluzzi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation